An efficient hybrid spectrum access algorithm in OFDM-based wideband cognitive radio networks - Yang, Chao; Fu, Yuli; Zhang, Yan; Yu, Rong; Liu, Yi (Neurocomputing (Amsterdam), 2014)
In cognitive radio networks, wideband spectrum sensing is a promising technology which allows a secondary user (SU) to detect the signals of primary users (PUs) over multiple channels, the sensing overhead is reduced effectively. Together with spectrum sensing, spectrum access strategy affects the system performance. In this paper, we propose an efficient hybrid access algorithm in OFDM-based wideband uplink model. An SU senses multiple channels via wideband spectrum sensing, and accesses these channels via a hybrid access strategy. The sensing time and transmission power of each channel are jointly optimized, in order to maximize the ergodic throughput of SUs, while the interferences to PUs are under the predefined thresholds. It is shown that the optimization problem can be formulated as a convex problem. Moreover, in order to reduce the computational complexity, two low complexity spectrum sensing and access schemes are proposed, in which the SU selects several specific channels to sense, and accesses all channels via a modified hybrid access strategy. For sensing channels selection, we present an effective selection criterion and an optimal selection order. Simulation results show that the proposed algorithm can effectively improve the system performance.